2011
DOI: 10.1016/j.molcel.2011.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Ecdysone- and NO-Mediated Gene Regulation by Competing EcR/Usp and E75A Nuclear Receptors during Drosophila Development

Abstract: SUMMARY The Drosophila ecdysone receptor (EcR/Usp) is thought to activate or repress gene transcription depending on the presence or absence, respectively, of the hormone ecdysone. Unexpectedly, we found an alternative mechanism at work in salivary glands during the ecdysone-dependent transition from larvae to pupae. In the absense of ecdysone, both ecdysone receptor subunits localize to the cytoplasm, and the heme-binding nuclear receptor E75A replaces EcR/Usp at common target sequences in several genes. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 38 publications
2
65
0
Order By: Relevance
“…A recent report (50) nicely demonstrated that SMRTER recruitment to ecdysone-inducible gene loci is mediated by E75, whose binding site overlaps with EcR/USP. Therefore, E75 likely suppresses the function of βFTZ-F1 in two ways: The first is through the traditional inhibitory interaction with the direct βFTZ-F1 inducer DHR3 (51, 65, 136), and the second is through the indirect counteracting effects on histone acetylation.…”
Section: Molecular Basis Of Stage- and Tissue-specific Responses To Ementioning
confidence: 94%
“…A recent report (50) nicely demonstrated that SMRTER recruitment to ecdysone-inducible gene loci is mediated by E75, whose binding site overlaps with EcR/USP. Therefore, E75 likely suppresses the function of βFTZ-F1 in two ways: The first is through the traditional inhibitory interaction with the direct βFTZ-F1 inducer DHR3 (51, 65, 136), and the second is through the indirect counteracting effects on histone acetylation.…”
Section: Molecular Basis Of Stage- and Tissue-specific Responses To Ementioning
confidence: 94%
“…However, RNAi-mediated knockdown of Trr, the Drosophila homolog of mammalian Mll3/Mll4, showed only a modest reduction in H3K4me2 and H3K4me3 levels in wing imaginal discs (Mohan et al 2011). These subtle changes in H3K4me2 and H3K4me3 are consistent with Trr regulating the activation of a subset of genes, such as the role of Trr in the transcriptional induction of ecdysone receptor target genes at promoter regions (Sedkov et al 2003;Johnston et al 2011). Depending on the developmental context and the requirement Figure 1.…”
mentioning
confidence: 93%
“…Similarly, the Trr/Mll3/Mll4 COMPASS-like complexes play an important role in hormone receptor-induced signaling. Upon hormonal induction, they are recruited to target promoters by nuclear hormone receptors, resulting in increased H3K4me3 and gene activation (Goo et al 2003;Sedkov et al 2003; Lee et al 2006;Mo et al 2006;Johnston et al 2011;Vicent et al 2011;Chauhan et al 2012). However, RNAi-mediated knockdown of Trr, the Drosophila homolog of mammalian Mll3/Mll4, showed only a modest reduction in H3K4me2 and H3K4me3 levels in wing imaginal discs (Mohan et al 2011).…”
mentioning
confidence: 99%
“…The nuclear receptor E75, an early puff gene in the ecdysone-signaling hierarchy, was found to contain a heme and to function as an NO sensor (Reinking et al 2005). In target tissues, NO acts by inhibiting the normally repressive activity of E75A (Johnston et al 2011). NO synthase activity is required in the PG to induce pupariation (Cáceres et al 2011).…”
Section: Nitric Oxide and E75mentioning
confidence: 99%